KANK1-NTRK3 fusions define a subset of BRAF mutation negative renal metanephric adenomas - Catic, Aida; Kurtovic-Kozaric, Amina; Sophian, Ardis; Mazur, Lech; Skenderi, Faruk; Hes, Ondrej; Rohan, Stephen; Rakheja, Dinesh; Kogan, Jillene; Pins, Michael R (BMC medical genetics, 2020)
BACKGROUND: Metanephric adenoma (MA) is a rare benign renal neoplasm. On occasion, MA can be difficult to differentiate from renal malignancies such as papillary renal cell carcinoma in adults and Wilms̕ tumor in children. Despite recent advancements in tumor genomics, there is limited data available regarding the genetic alterations characteristic of MA. The purpose of this study is to determine the frequency of metanephric adenoma cases exhibiting cytogenetic aberration t (9;15)(p24;q24), and to investigate the association between t (9,15) and BRAF mutation in metanephric adenoma. METHODS: This study was conducted on 28 archival formalin fixed paraffin-embedded (FFPE) specimens from patients with pathologically confirmed MA. Tissue blocks were selected for BRAF sequencing and fluorescent in situ hybridization (FISH) analysis for chromosomal rearrangement between KANK1 on chromosome 9 (9p24.3) and NTRK3 on chromosome 15 (15q25.3), which was previously characterized and described in two MA cases. RESULTS: BRAFV600E mutation was identified in 62% of our cases, 9 (38%) cases were BRAFWT, and 4 cases were uninformative. Of the 20 tumors with FISH results, two (10%) were positive for KANK1-NTRK3 fusion. Both cases were BRAFWT suggesting mutual exclusivity of BRAFV600E and KANK1-NTRK3 fusion, the first such observation in the literature. CONCLUSIONS: Our data shows that BRAF mutation in MA may not be as frequent as suggested in the literature and KANK-NTRK3 fusions may account for a subset of BRAFWT cases in younger patients. FISH analysis for KANK1-NTRK3 fusion or conventional cytogenetic analysis may be warranted to establish the diagnosis of MA in morphologically and immunohistochemically ambiguous MA cases lacking BRAF mutations.
Keywords: senioři; fúzní onkogenní proteiny; Chromosomal translocations; hybridizace in situ fluorescenční; lidé; Oncogene Proteins, Fusion; mladiství; lidské chromozomy, pár 9; KANK1-NTRK3 fusion; adaptorové proteiny signální transdukční; Middle Aged; mužské pohlaví; mutace; receptor trkC; adenom; Adult; mladý dospělý; Adenoma; Kidney Neoplasms; dítě; In Situ Hybridization, Fluorescence; Metanephric adenoma; Child; lidské chromozomy, pár 15; BRAFV600E; Receptor, trkC; Young Adult; ženské pohlaví; Mutation; Adaptor Proteins, Signal Transducing; Cytoskeletal Proteins; Humans; cytoskeletální proteiny; Cytogenetics; Proto-Oncogene Proteins B-raf; Chromosomes, Human, Pair 9; lidé středního věku; protoonkogenní proteiny B-Raf; Chromosomes, Human, Pair 15; Translocation, Genetic; dospělí; translokace genetická; Female; Aged; Adolescent; nádory ledvin; Male